Specification of Actual Evapotranspiration in Iraq by GIS - Al Rammahi, Ali Hussein Jaber (Iraqi Journal of Science, 2021)
Evapotranspiration (ET) is produced from vegetation transpiration and soil evaporation. The ET measurements must be considered to study water management systems and irrigation (planning, designing and operating). This study is based on USGS (United States Geological Survey) data by the SSEBop (Simplified Surface Energy Balance) model to estimate the total annual amount of ET using ArcGIS software. The ET values were determined for seventeen years from 2003 to 2019. Also, these values for year 2020 were estimated based on the value of the monthly ET for seven months, i.e. until August by summation. The field data of gauge stations spread throughout Iraq for the year 2012 were used to verify the ET values for the same year. There was distinct compatibility between them. For the four years 2017, 2018, 2019 and 2020, the area of zero ET was a little more than half the area of Iraq (56%). While the years from 2003 to 2016, the average percentage of the area was about 24% of Iraq’s area. For classification for ET values 0 - 50 mm, the area percentage was 29% of total area for years from 2003 to 2016, while from 2017 to 2020 the percentage was 10%. The ET values of 50-100 mm have an area ratio of 12% of total area for years 2003 to 2016, while the percentage was 4% for the remaining years. For all years of study, the area percentage was approximately the same for ET values greater than 100 mm. The study recommends increasing the water quotas and speeding up the construction of strategic projects in Iraq to compensate the shortage of vegetation cover, especially in last the four years, more than half of the area had ET values equal to zero.